East Anglian English in the English Dialects App: Regional variation in East Anglian English based on evidence from a smartphone-based survey. Issue 3 (September 2020) - Britain, David; Blaxter, Tamsin; Leemann, Adrian
Abstract : East Anglian English was the first British variety of English to be subject to dialectological scrutiny using sociolinguistic techniques (Trudgill, 1974, and his subsequent work) and since then has been subject to only sporadic investigation (e.g. Britain, 1991, 2014a, 2014b, 2015; Kingston, 2000; Straw, 2006; Amos, 2011; Potter, 2012, 2018; Butcher, 2015). Recent research has suggested that, in those few locations that have been investigated, East Anglian English is gradually losing some of its traditional dialect features, in favour of forms from the South East more generally. Kingston (2000), Britain (2014a) and Potter (2018) all found, for example, a rather steep decline in the use of East Anglia's traditional third-person present-tense zero. Furthermore, we are aware of the arrival into East Anglia of linguistic innovations from the South East of England, such as TH fronting (Trudgill, 1988; Britain, 2005; Potter, 2012) and /l/ vocalisation (Johnson & Britain, 2007; Potter, 2014), but we only know about their success in a few parts of the region – Norwich, East Suffolk and the Fens. Since Trudgill's investigations across East Anglia in the 1970s, however (e.g. Trudgill & Foxcroft, 1978), and despite a few multilocality studies (Britain, 1991, 2014a; Potter, 2018) no research has been able to provide a picture of the state of the traditional dialect across the whole region . We have therefore only a patchy understanding of the extent to which traditional dialect obsolescence, dialect levelling and innovation diffusion have impacted the dialect landscape of this region as a whole.